The impact of perceived school climate on exercise behavior engagement among obese adolescents: a dual mediation effect test of exercise benefits and perseverance qualities - Yin, Yao; Zhang, Chong; Chen, Zhibo; Qi, Yufei; Qiu, Cheng (Frontiers in Psychology, 2023)
This study explores the relationship between perceived school climate and exercise behaviour among obese adolescents, as well as the multiple mediating effects of perseverance qualities and exercise benefits. Methods: A survey was conducted on 586 obese adolescents in Beijing, with an age range of 13-18 years old and an average age of 15.40±1.824, among who 337 were male, 249 were female, 303 were high school students and 238 were middle school students. A standard scale was used to evaluate perceived school climate, exercise benefits, perseverance qualities, and exercise behaviours. The data was analyzed by independent samples t-test, bivariate correlation analysis, descriptive statistical analysis, and structural equation model (SEM). Results: (1) Perceived school climate among obese adolescents positively predicted exercise behaviour (Z=2.870,P<0.01), perseverance qualities (Z=3.107,P<0.01) and exercise benefits (Z=4.290,P<0.001); perseverance qualities positively predicted exercise behaviour in obese adolescents (Z=4.431,P<0.001); exercise benefits positively predicted the obese adolescents' exercise behaviour (Z=4.267,P<0.001); (2) Perseverance qualities (Z=2.282,95% CI [0.032, 0.191], [0.028,0.179]) and exercise benefits (Z=2.518,95% CI [0.060, 0.287], [0.053,0.271]) play a mediating role in the obese adolescents' perceived school climate and exercise behavior respectively. These two factors have parallel multiple mediating effects between obese adolescents' perceived school climate and exercise behaviour, with mediating effects accounting for 16% and 25% respectively. The mediating effect of exercise benefits is greater than that of perseverance qualities; (3) There is no difference in the specific indirect effects of perseverance qualities and exercise benefits (Z = -0.800, 95% CI [-0.198, 0.064], [-0.190,0.068]). Conclusion: Obese adolescents' perception of school climate can effectively enhance their motivation to participate in exercise behaviour and indirectly influence exercise behaviour through exercise benefits and perseverance qualities, cultivate good physical exercise behavior among obese adolescents, and effectively prevent and intervene in the occurrence of obesity.